Plant growth evaluation of Cajanus cajan (L.) Millsp., Canavalia ensiformis (L.) DC. and Cratylia argentea (Desvaux) O. Kuntze., in soils degraded by sand and gravel extraction (2017)
In this research, the adaptability of pigeon pea (Cajanus cajan (L.) Millsp., canavalia (Canavalia ensiformis (L.) DC.) and veranera (Cratylia argentea (Desvaux) O. Kuntze) species, was evaluated in soils degraded by sand and gravel extraction. The three species were planted in bags as follows: 20 x 10cm, each with 3 seeds, with a substrate 2:1 soil and sand, respectively. The plants were grown under shadow conditions with 50% for 60 days, and received irrigation according to climate conditions. Therefore, were transplanted at field conditions, plant height (PH), fully developed leaves (FDL) and stem diameter (SD) variables, were measured every week for 10 weeks. A randomized block design was used with a fixed balanced effect. The number of replicates per treatment was four, the multivariate technique MANOVA variance with orthogonal type was included and the method of maximum likelihood was used to establish the dimensionality of the contrast. In fact, one-dimensional comparisons were carried out using Tukey method, which had achieved type I error of 5% statistical significance. Significant difference among plants for PH (p0.05) variable was obtained. In addition, SD variable showed differences from the third week for all evaluated plants (p0.05). A highly significant and directly proportional relationship among HP, FDL and SD variables (p0.0001), was found. MANOVA Multivariate Analysis showed a highly significant difference among evaluated species (p0.0001), which confirms the hypothesis. It was expected that species were developing and growing despite having contrasting conditions in the study area.